SEA302 - Economic Transformation in Southeast Asia Mac 2002 - PPSKM, Pusat Pengajian Sains Kemasyarakatan (Universiti Sains Malaysia, 2002)
UNIVERSITI SAINS MALAYSIA Second Semester Examination Academic Session 2001/2002 February/Mac 2002 SEA302 -Economic Transformation in Southeast Asia Duration: 3 hours Answer FOUR (4) questions; you must answer ONE (1) question from each section. Begin your answer to each question on a new booklet. All questions carry equal marks (25 marks).